The son of man in the Gospel of John - Ellens, J. Harold (New Testament monographs, 2010)
Introduction -- The son of man in John -- The son of man in the Synoptic Gospels -- Comparison of the son of man in John and in the Synoptic Gospels, in the light of Second Temple Judaism son of man traditions -- Summary and conclusion